2009
DOI: 10.1007/s00439-009-0729-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel quantitative trait loci for central corneal thickness identified by candidate gene analysis of osteogenesis imperfecta genes

Abstract: Osteogenesis imperfecta (OI) is a rare connective tissue disorder caused by mutations in the type I collagen genes, COL1A1 and COL1A2, and is characterised by low bone mass and bone fragility. In this study, we explored the relationship between type 1 collagen genes and the quantitative trait central corneal thickness (CCT). CCT was measured in a cohort of 28 Australian type I OI patients and mean CCT was found to be significantly lower compared to a normal population (P < 0.001). We then investigated CCT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 41 publications
(41 reference statements)
2
21
0
Order By: Relevance
“…It is well-known that the severity of OI varies even among patients in the same family Witecka et al, 2008;Basel and Steiner, 2009;Brooks et al, 2009;Dimasi et al, 2010). In this study, phenotypic variability was also observed between family 1 and family 2 as well as among patients in each family.…”
Section: Discussionsupporting
confidence: 71%
“…It is well-known that the severity of OI varies even among patients in the same family Witecka et al, 2008;Basel and Steiner, 2009;Brooks et al, 2009;Dimasi et al, 2010). In this study, phenotypic variability was also observed between family 1 and family 2 as well as among patients in each family.…”
Section: Discussionsupporting
confidence: 71%
“…A reduction in central corneal thickness (CCT) has been observed in a number of systemic and ocular diseases, including Ehlers-Danlos syndrome, osteogenesis imperfecta, keratoconus, and brittle cornea syndrome. [1][2][3][4] Reduced CCT has also been associated with an increased risk of primary open-angle glaucoma (POAG), the second leading cause of blindness worldwide. 5,6 In POAG, CCT has been shown to be a risk factor independent of other known risk factors, including advanced age and elevated intraocular pressure (IOP), and has been linked with increased disease severity and rapid disease progression.…”
Section: Resultsmentioning
confidence: 99%
“…Mounting evidence suggests central corneal thickness (CCT) plays a significant factor in ocular health. Thin CCT has been observed in several visual disorders, including brittle cornea syndrome, keratoconus, and osteogenesis imperfecta (1)(2)(3). CCT is also an important endophenotype for primary open angle glaucoma (POAG).…”
Section: Introductionmentioning
confidence: 99%